Synthesis and Catalytic Performance of Gold Intercalated in the Walls of Mesoporous Silica - Ji, Yazhou (J Vis Exp, 2015)
As a promising catalytically active nano reactor, gold nanoparticles intercalated in mesoporous silica (GMS) were successfully synthesized and properties of the materials were investigated. We used a one pot sol-gel approach to intercalate gold nano particles in the walls of mesoporous silica. To start with the synthesis, P123 was used as template to form micelles. Then TESPTS was used as a surface modification agent to intercalate gold nano particles. Following this process, TEOS was added in as a silica source which underwent a polymerization process in acid environment. After hydrothermal processing and calcination, the final product was acquired. Several techniques were utilized to characterize the porosity, morphology and structure of the gold intercalated mesoporous silica. The results showed a stable structure of mesoporous silica after gold intercalation. Through the oxidation of benzyl alcohol as a benchmark reaction, the GMS materials showed high selectivity and recyclability.